1998
DOI: 10.1001/jama.280.11.989
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Licensing Examination Scores and Resource Use and Quality of Care in Primary Care Practice

Abstract: Context.-Clinical competence is a determinant of the quality of care delivered, and may be associated with use of health care resources by primary care physicians. Clinical competence is assumed to be assessed by licensing examinations, yet there is a paucity of information on whether scores achieved predict subsequent practice. Objective.-To determine if licensing examination scores were associated with selected aspects of quality of care and resource use in initial primary care practice. Design.-Prospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0
5

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(97 citation statements)
references
References 74 publications
2
90
0
5
Order By: Relevance
“…Several groups have assessed the predictive validity of other high‐stakes medical examinations, including the United States Medical Licensing Examination ® (USMLE ® )8, 9, 10, the Quebec Licensing Examination11, the Medical Council of Canada Qualifying Examination12, 13, 14, the MRCP examination15, 16, 17 and Membership of the Royal College of General Practitioners examination15. Performance in these examinations predicts performance in clinical practice and other medical assessment processes11 18, 19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups have assessed the predictive validity of other high‐stakes medical examinations, including the United States Medical Licensing Examination ® (USMLE ® )8, 9, 10, the Quebec Licensing Examination11, the Medical Council of Canada Qualifying Examination12, 13, 14, the MRCP examination15, 16, 17 and Membership of the Royal College of General Practitioners examination15. Performance in these examinations predicts performance in clinical practice and other medical assessment processes11 18, 19.…”
Section: Discussionmentioning
confidence: 99%
“…Performance in these examinations predicts performance in clinical practice and other medical assessment processes11 18, 19. For example, each part of the MRCP examination predicts the next17, and candidates who score higher in all parts of the MRCP examination do better in workplace‐based assessments than those who underperform16.…”
Section: Discussionmentioning
confidence: 99%
“…8 Eva and Lingard's recommendations are to aggregate forces and skills in research centres, and to view scientific progress not as the single important study but as the multi-year program of research that allows broader exploration of topics. 5 Over multiple years and studies, Tamblyn et al documented the relationship between scores on the Canadian provincial licensing examination and attributes of physicians' performance in practice, [95][96][97][98][99] and in their seminal work, they have shown that a focused body of high-quality research can create a scientific foundation for medical education and assessment. A future cohesive body of research to close the gap at the interface of medical education and practice could be similar to the research in hematology/oncology being organized around the Cancer and Leukemia Group B as a way to overcome the limitations of small local samples of cancer patients through pooled data and collaborative research for more than four decades.…”
Section: Scientific Theory In Medical Education Researchmentioning
confidence: 99%
“…Furthermore, should the outcomes for a high-priced lawyer, who can select his or her clients, be compared to the outcomes for a public defender? While data are available that might be used in such evaluations (e.g., rates of death or guilty verdicts) and several such studies have been conducted (e.g., Norcini et al, 2002;Tamblyn et al, 1998Tamblyn et al, , 2002, many factors can contribute to the outcomes, making interpretation of the relationships very tricky.…”
Section: Box 2-1 Terminology: Licensure Versus Certificationmentioning
confidence: 99%
“…Although there are a few situations in which such evidence has been collected (e.g., Norcini, Lipner, and Kimball, 2002;Tamblyn et al, 1998Tamblyn et al, , 2002, in most cases, no adequate criterion is available, and, in practice, the outcomes depend on many variables beyond the competence of the individual practitioner. Even the best driver can get into accidents, and even the best neurologist will not be successful in every case.…”
Section: Criterion-related Validity Evidencementioning
confidence: 99%